DETERMINATION OF LEAD(II) USING LUCIGENIN-H2O2-OH- SYSTEM VIA FLOW INJECTION-CHEMILUMINESCENCE - العوادي نغم (Iraqi Journal of Science, 2024)
A new mode in the Semi-automated on-line analysis for lead(II) via chemiluminescence system of Lucigenin-H2O2-OH–Lead(II) which gives a blue-green chemiluminescence, when Lucigenine is oxidized by hydrogen peroxide in alkaline medium was studied. Measurement of the generated light in a flat-spiral glassy cell designed for this purpose were achieved using advanced electronic detection system (with a multiple choice of readout systems). A relation for the variation of response with concentration expand from 1-15 g.ml-1 with %linearity of 97.6% while a % of linearity 99.44% using a quadratic equation. The quadratic equation represent the data much more preferably in which a picogram level of detection limit was achieved. Also the study was carried out for interferring effect.